METHOD FOR PRODUCING LINEAR OR BRANCHED FATTY ACID ESTERS BY MEANS OF HETEROGENEOUSLY CATALYSED REACTIVE RECTIFICATION WITH AN UPSTREAM REACTOR - ROESSLER, HARALD; TOPPHOFF, MAGNUS; REUTER, ERICH; GUTSCHE, BERNHARD (2004)
Vorgeschlagen wird ein Verfahren zur kontinuierlichen Veresterung von C1-C22-(Fett)säuren mit C1-C10-Monoalkanolen, C2-C5- Di- bzw. Trialkanolen, oder Mischungen hiervon, in flüssiger Phase im Gegenstromverfahren, in Gegenwart von heterogenen Katalysatoren im Vorreaktor (1) und in der Reaktionskolonne (3), dadurch gekennzeichnet, dass ein Vorreaktor (1) und eine Abtrenneinheit (2) der Reaktionskolonne (3) zur Verringerung der Viskosität des Reaktionsgemisches vorgeschalte wird und über die Abtrenneinheit (2), zur Verschiebung des Reaktionsgleichgewichts vor der Reaktionskolonne (3) das Reaktionswasser aus dem System entfernt wird. The invention relates to a method for the continuous esterification of C1-C22 (fatty) acids with C1-C10 monoalcohols, C2-C5 dialkanols or trialkanols, or mixtures thereof, in the liquid phase, according to the counterflow method, in the presence of heterogeneous catalysts in the upstream reactor (1) and in the reaction column (3). Said method is characterised in that an upstream reactor (1) and a separating unit (2) are mounted upstream of the reaction column (3), in order to reduce the viscosity of the reaction mixture, and the reaction water (3) is extracted from the system by means of the separation unit (2), in order to shift the chemical balance upstream of the reaction column (3). L'invention concerne un procédé d'estérification continue de C1-C22 acides (gras) à l'aide de C1-C10 monoalcanols, de C2-C5 dialcanols ou trialcanols, ou de mélanges de ceux-ci, en phase liquide, selon le procédé à contre-courant, en présence de catalyseurs hétérogènes dans le réacteur amont (1) et dans la colonne de réaction (3). Le procédé selon l'invention est caractérisé en ce qu'un réacteur amont (1) et une unité de séparation (2) sont placés en amont de la colonne de réaction (3) afin de réduire la viscosité du mélange de réaction, et en ce que l'eau de réaction est extraite du système à l'aide de l'unité de séparation (2) afin de déplacer l'équilibre de réaction en amont de la colonne de réaction (3).